Analyse des Pontes de la Spongieuse, Lymantria dispar L. (Lepidoptera, Lymantriidae) sur Chêne Liège (Blida-Algérie) - Mecellem, Dalila; Chakali, Gahdab (Silva Lusitana, 2012)
In the last infestation of Gypsy moth, counting and egg mass biometrics were conducted in Bouarfa cork oak forest. The comparison of means showed a high significance between eggs mass quantified during the years 2007 and 2008 with respective averages of 135 and 29 per tree. At the second year, eggs mass measurements and quantification of eggs laid have found significant reduction surface of 40% and the 65% average number of eggs. Frequency analysis of surfaces and the number of eggs have revealed five classes for the two generations considered. The data confirm the typical pattern of a gradation of Lymantria dispar.
Keywords: Algeria; Blida; egg mass; Gypsy moth

Preliminary Survey of the Occurrence of Entomopathogenic Nematodes and Fungi in the Forest Soils of Algeria - Zamoum, Mohamed; Berchiche, Sabiha; Sai, Karima; Triggiani, Oreste; Tarasco, Eustachio (Silva Lusitana, 2011)
The natural distribution and diversity of entomopathogenic nematodes (EPN) and fungi (EPF) in various biotopes in Algeria was studied, particularly in forests and plantations of cedar, oak, pine, eucalyptus and palm. The objective of this study was to identify EPN and/or EPF species which could be used to control forest insect pests. Soil sampling was carried out at 223 sites from April 2007 to March 2008. To trap EPN's juvenile larvae of Steinernematidae and Heterorhabditidae and EPF, the method of "insect-trap" was used in the laboratory. Caterpillars of Galleria mellonella (Lep., Pyralidae) and the forest insects Thaumetopoea pityocampa (Lep., Thaumetopoeidae) and Lymantria dispar (Lep. Lymantriidae) were used. The presence of EPN was noted in 8.1% of the sampled sites and EPF in 9.9%. The presence of the EPN in the oasis biotope may result from particular microclimate conditions (of temperature and humidity). Nematodes belonging to the Steinernematidae family and Steinernema genus were identified. In addition, 10 fungal species were isolated, namely:Beauveria bassiana, Fusarium sp., Alternaria sp., Penicellium sp., Trichoderma sp., Sordaria sp., Mucor sp., Chaetomium globosum, Aspergillus nigricans and Rhizopus nigricans. The majority of the fungi were isolated in the conidian form, except for Chaetomium globosum which had its perfect form with perithecia. The presence of EPN and EPF seems to depend on the dominant species of forest trees, either cork oak (35%), cedar (12.5%), pine (12.5%), palm (10%) or eucalyptus (7.5%).
Keywords: Algeria; biological control; Entomopathogenic; forest insect pests; fungi; nematodes

Diversité floristique des suberaies du Parc National de Tlemcen (Algerie - Letreuch-Belarouci, A. (Acta botánica malacitana, 2009)
The analysis of the ﬂoristic diversity of forest massif “Haﬁr-Zariffet” in the Tlemcen National Park has revealed the existence of 211 taxa which belong to 65 families and 164 genera. The number of taxa endemic and/or rare includes: 1 endemic algerian, 7 algero-moroccan, 11 ibero-algero-moroccan, 7 are endemic in North Africa and 11 are endemic in Iberian Peninsula and North Africa. The number of rare taxa is 26, 9 are at the same time threatened. Urgent efforts are required to preserve the cork oak as well as endemic species conﬁned to it.
Keywords: Algeria; Cork Oak Forest; diversity; Inventory; national park of tlemcen

Fire effects on the composition of Pinus halepensis and Quercus rotundifolia communities in the Bou-Taleb Forest, Algeria, with application of a multivariable analysis - Madoui, Amar; Goldammer, Johann G (Forest Ecology and Management, 2006)
The effect of forest ﬁre on the ﬂora of Bou-Taleb’s forest was studied using a Factorial Correspondence Analysis (FCA). This analysis, implemented by using the Braun-Blanquet method, was applied on ﬂoristic releves investigated on Aleppo pine (Pinus halepensis) and on Holm oak (Quercus rotundifolia) communities which burned at different dates. Other ones represent the non-burnt communities and were used as control. Two analyses were used with all releves (160) and all the species which f > 1 (323). The ﬁrst analysis is applied with a presence-absence coefﬁcient and the second one with an abundance-dominance coefﬁcient. The third analysis involved only releves of burned communities (98) and all species (361). The results of all analyses show the time elapsed since ﬁre (ﬂoristic age) is a discrimination factor. We found a clear separation of young communities on the one side, which appeared immediately after ﬁre, and older communities on the other side. Also, ﬁre effects were linked to the type of communities. There is a distinct difference between Aleppo pine and Holm oak communities. There is invasion of therophytes on the parcels recently burned. Few years after ﬁre, the ﬂoristic composition and structure of communities will be the same as on unburned sites.
Keywords: Aleppo pine; Algeria; FCA; Forest ﬁres; Holm oak; Pinus halepensis; Quercus rotundifolia

Fire effects on the composition of Pinus halepensis and Quercus rotundifolia communities in the Bou-Taleb Forest, Algeria, with application of a multivariable analysis - Madoui, Amar; Goldammer, Johann G. (Forest Ecology and Management, 2006)
The effect of forest ﬁre on the ﬂora of Bou-Taleb’s forest was studied using a Factorial Correspondence Analysis (FCA). This analysis, implemented by using the Braun-Blanquet method, was applied on ﬂoristic releves investigated on Aleppo pine (Pinus halepensis) and on Holm oak (Quercus rotundifolia) communities which burned at different dates. Other ones represent the non-burnt communities and were used as control. Two analyses were used with all releves (160) and all the species which f > 1 (323). The ﬁrst analysis is applied with a presence-absence coefﬁcient and the second one with an abundance-dominance coefﬁcient. The third analysis involved only releves of burned communities (98) and all species (361). The results of all analyses show the time elapsed since ﬁre (ﬂoristic age) is a discrimination factor. We found a clear separation of young communities on the one side, which appeared immediately after ﬁre, and older communities on the other side. Also, ﬁre effects were linked to the type of communities. There is a distinct difference between Aleppo pine and Holm oak communities. There is invasion of therophytes on the parcels recently burned. Few years after ﬁre, the ﬂoristic composition and structure of communities will be the same as on unburned sites.
Keywords: Aleppo pine; Algeria; FCA; Forest ﬁres; Holm oak; Pinus halepensis; Quercus rotundifolia

PRELIMINARY DATA ON THE ECOLOGY OF WOODMOUSE APODEMUS-SYLVATICUS LINNE, 1758, NEAR TALA-GUILEF, DJURDJURA-NATIONAL-PARK ALGERIA - HAMDINE, W; POITEVIN, F (REVUE D ECOLOGIE-LA TERRE ET LA VIE, 1994)
Wood mice (n = 166) were sampled in 1989-1990 by line trapping in the Djurdjura National Park, Algeria. Most were observed in forests of sclerophyllous oaks (Quercus ilex, Quercus suber) and in mountain grasslands. The species was scarcer in cedar forests. Most (70 %) of the captured individuals were adults with a large number of males. Furthermore, most of the individuals were captured in spring (ca. 52 %).
Keywords: Algeria; Apodemus sylvaticus; Ecological abundance; Plant cover; population structure; seasonal variation; Sex ratio